Self-assessment in a professional master's degree in health promotion: the perception of graduates (Research, Society and Development, 2023)
The Stricto Sensu Graduate Programs in the Professional modality, as well as the Master's Program in Health Promotion at the Centro Universitário Adventista de São Paulo (UNASP), are committed to presenting social, scientific and technological relevance in the processes of professional training. This article aims to investigate the biannual result of the evaluation process in a Professional Master's Degree in Health Promotion carried out by the Self-Assessment Committee. In 2020 and 2021, questionnaires formulated based on CAPES evaluation guidelines were sent to graduates of the Master's degree in Health Promotion. The graduates responded and sent their responses to the survey via email, which were statistically analyzed from the graduates' perspective on the quality experienced in the Stricto Sensu Graduate Program in the Program, Training and Impact on Society dimensions. The Self-Assessment questionnaires were applied electronically in 2020 and 2021, with the respective feedback organized by the Self-Assessment Commission in 2021 and 2022. The results show a significant increase in the proportion of technical and technological productions - from regular to good and from good to very good were p=0.004 and p=0.003, respectively. We understand, therefore, that the evaluation process subsidizes reflections and changes in the direction of qualitative results agreed upon by all.